Coherence Method in Matan Criticism - Ahmad Musyafiq (UIN Sunan Kalijaga Yogyakarta, 2019)
This paper aims to formulate the application of the coherence method known in philosophy to the matan criticism. This formulation is important for several reasons. First, the science of hadith as one of the Islamic sciences has been dominated by awareness of its normative dimensions compared to the dimensions of its historicity. Second, in addition to differences there are similarities between the coherence method and the matan criticism, namely in terms of seeking the truth by relying on certain standard.The application of the coherence method in this matan criticism is carried out in three main steps. First, determining the criteria for religious truth that will be used as benchmarks. In this case, the criteria of truth chosen are contemporary maqashid al-sharia, especially in the perspective of Jasser Audah. Second, mapping the theme of the hadith being studied, to facilitate synchronization with the selected criteria of truth. Third, interpreting the hadith that is being studied based on Ulumul Hadith in general and ‘Ilm Ma’ani al-Hadith in particular, by utilizing the latest theories from the sciences related to the hadith being studied.The implications of applying this method can at least be seen through two things, which are at the same time the goal of the formulation of this method. First, the reduction of the awareness domination of the normative dimension in matan criticism. This will have an impact on increasing awareness of the dimensions of historicity and humanity in matan criticism and is expected to contribute to the reduction of exclusive and radical attitudes. Second, integration or at least interconnection between two methods of seeking truth from two different disciplines, namely Hadith and Philosophy.This paper aims to formulate the application of the coherence method known in philosophy to the matan criticism. This formulation is important for several reasons. First, the science of hadith as one of the Islamic sciences has been dominated by awareness of its normative dimensions compared to the dimensions of its historicity. Second, in addition to differences there are similarities between the coherence method and the matan criticism, namely in terms of seeking the truth by relying on certain standard.The application of the coherence method in this matan criticism is carried out in three main steps. First, determining the criteria for religious truth that will be used as benchmarks. In this case, the criteria of truth chosen are contemporary maqashid al-sharia, especially in the perspective of Jasser Audah. Second, mapping the theme of the hadith being studied, to facilitate synchronization with the selected criteria of truth. Third, interpreting the hadith that is being studied based on Ulumul Hadith in general and ‘Ilm Ma’ani al-Hadith in particular, by utilizing the latest theories from the sciences related to the hadith being studied.The implications of applying this method can at least be seen through two things, which are at the same time the goal of the formulation of this method. First, the reduction of the awareness domination of the normative dimension in matan criticism. This will have an impact on increasing awareness of the dimensions of historicity and humanity in matan criticism and is expected to contribute to the reduction of exclusive and radical attitudes. Second, integration or at least interconnection between two methods of seeking truth from two different disciplines, namely Hadith and Philosophy.